Exploration of Misbah's Tafsir on the Role of Education in Character Formation - Muhammad Akmal Jauhar Rifqi; Andri Nirwana AN; Yeti dahliana; Kharis Nugroho; Ainur Ra’in; Syamsul Hidayat (al-Afkar, Journal For Islamic Studies, 2024)
Tafsir Al-Misbah, written by Prof. Dr. M. Quraish Shihab, offers an in-depth perspective on the teachings of the Koran related to character education. Through the analysis of the content of this interpretation, research identifies the main values taught in the Qur'an, such as honesty, justice, responsibility, and respect, as well as the educational methods recommended to instill these values in individuals. This research also explores the relevance and application of these teachings in the context of modern education. The research results show that education based on the values of the Koran, as explained in the interpretation of Al-Misbah, has great potential in forming quality individual characters and noble morals. This education not only focuses on intellectual development, but also on moral and spiritual development, which ultimately contributes to the formation of a better society.